Optimization of Microwave-Assisted Extraction of Polysaccharides from Ulva pertusa and Evaluation of Their Antioxidant Activity - Bao Le; Kirill S. Golokhvast; Seung Hwan Yang; Sangmi Sun (MDPI AG, 2019)
The use of green marine seaweed Ulva spp. as foods, feed supplements, and functional ingredients has gained increasing interest. Microwave-assisted extraction technology was employed to improve the extraction yield and composition of Ulva pertusa polysaccharides. The antioxidant activity of ulvan was also evaluated. The impacts of four independent variables, i.e., extraction time (X1, 30 to 60 min), power (X2, 500 to 700 W), water-to-raw-material ratio (X3, 40 to 70), and pH (X4, 5 to 7) were evaluated. The chemical structure of different polysaccharides fractions was investigated via FT-IR and the determination of their antioxidant activities. A response surface methodology based on a Box–Behnken design (BBD) was used to optimize the extraction conditions as follows: extraction time of 43.63 min, power level of 600 W, water-to-raw-material ratio of 55.45, pH of 6.57, and maximum yield of 41.91%, with a desired value of 0.381. Ulvan exerted a strong antioxidant effect against 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and showed reducing power in vitro. Ulvan protected RAW 264.7 cells against H2O2-induced oxidative stress by upregulating the expression and enhancing the activity of oxidative enzymes such as superoxide dismutase (SOD) and superoxide dismutase (CAT). The results suggest that the polysaccharides from U. pertusa might be promising bioactive compounds for commercial use.